The interlinked history of exotic vegetables production and urban farming in Ghana - Drechsel, Pay (RUAF Global Partnership on Sustainable Urban Agriculture and Food Systems, 2025)
The Ghanaian diet features a mixture of indigenous and “exotic” fruits and vegetables first cultivated by pre-colonial settlers in the 15th century. This article explains how exotic urban vegetable farming took root to satisfy the tastes of traders, and led to strong European influence in Ghana’s modern day food culture.